Studi Evaluasi Pemahaman Siswa Sekolah Dasar Kelas VI Terhadap Mata Pelajaran Matematika - R. Rami Sartika (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The purpose of this study was to find out how well grade 5 students at SDN 037 Bakau Aceh understand mathematics subjects. This research uses a type of qualitative research known as a case study. The validity test showed that 15 questionnaire questions from the questionnaire based on respondents' answers were invalid and 5 questionnaire questions had a correlation value greater than 0.05. In addition, reliability determines that all questions in the questionnaire based on respondents' answers are reliable with a significance level of 5%. Among students' understanding in mathematics subjects is that students have the ability to explain back learning outcomes, are able to develop concepts that have been learned in a structured manner, are able to provide examples to their friends related to learning material according to the context of discussion, and are able to interpret concepts systematically so that they can relate them to each other in everyday life.